2012
DOI: 10.23850/22565035.25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de impacto ambiental producido por el uso de cocinas tradicionales en el área de conservación regional Vilacota-Maure de la región Tacna

Abstract: El 70 % de la población de las zonas rurales, interandinas y altoandinas en el Perú usa biomasa para calefacción, cocción y otras labores artesanales ycostumbristas. Es necesario disponer de datos sobre la extracción, el consumo de biomasa y los impactos que pueden estar provocando, para planificar suproducción y utilización sostenibles. Este trabajo es producto de varios años de investigación. Las condiciones geográficas, climáticas y culturales de la zona en estudio impiden realizar unaestadía prolongada par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Figure 11 shows the exponential relationship between the number of trees saved and the amount of CO 2 emissions that each of them represents. From a study on the environmental impact of firewood, by Peruvian researchers Torres, H. and Polo, C., with the collaboration of scientists Seifert, D. and Neuoetting, D., it has been found that 1 kg of firewood emits 1.83 kg CO 2 , since half the wood's mass is carbon (C) and its relation with the molecular weight of CO 2 is 44/12, thus 1 kg of firewood produces 0.5 (44/12 kg of CO 2 ) = 1.83 kg of CO 2 [30].…”
Section: Comparison Of Energy Characteristics For Both Fuelsmentioning
confidence: 99%
“…Figure 11 shows the exponential relationship between the number of trees saved and the amount of CO 2 emissions that each of them represents. From a study on the environmental impact of firewood, by Peruvian researchers Torres, H. and Polo, C., with the collaboration of scientists Seifert, D. and Neuoetting, D., it has been found that 1 kg of firewood emits 1.83 kg CO 2 , since half the wood's mass is carbon (C) and its relation with the molecular weight of CO 2 is 44/12, thus 1 kg of firewood produces 0.5 (44/12 kg of CO 2 ) = 1.83 kg of CO 2 [30].…”
Section: Comparison Of Energy Characteristics For Both Fuelsmentioning
confidence: 99%
“…Solo un pequeño porcentaje de los lugareños (1,7 %) se dedica al pastoreo de animales en el valle de los Géiseres. Esta actividad ganadera se realiza fuera del ecosistema, asegurando así la salud de los animales y constituyendo su única fuente de ingresos (Torres et al, 2010).…”
Section: Discussionunclassified
“…This activity is often stigmatised as environmentally destructive and also associated with low-income people (Morales et al 2017). For this reason, the issue is generally approached from a conservationist perspective, analysing the negative environmental impact of firewood use on native forests (Contreras-Hinojosa et al 2003, Ramos & Albuquerque 2012, Torres Muro et al 2010. From this perspective, firewood collection is considered an activity incompatible with the conservation of native vegetation in reserve areas (Doumecq 2019).…”
Section: Introductionmentioning
confidence: 99%